Catalogue of the Byzantine coins in the Dumbarton Oaks Collection and in the Whittemore Collection. Vol. II : Phocas to Theodosius III, 602-717. Pt. 1 : Phocas and Heraclius, 602-641. - Grierson, Philip. (Washington)
viii, 383 s., xxii s. res.